Apocalyptic interpretation of the Bible : apocalypticism and Biblical interpretation in early Judaism, the Apostle Paul, the historical Jesus and their reception history /: apocalypticism and Biblical interpretation in early Judaism, the Apostle Paul, the historical Jesus and their reception history. (2012) - Oegema, Gerbern S, 1958-
No abstract available